The Implementation of Aqidah Akhlak Teachers in Addressing Bullying Cases at Mts. Darut Taqwa 02 Purwosari Pasuruan - Mashabi, M. Ali; 'Athiyyah, Avita Aniqotul (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3718, 2025)
Mts. Darut Taqwa 02 Purwosari Pasuruan is a junior high school educational institution located under the auspices of the pondon of pesantren ngalah Purwosari Pasuruan, which is located in the yellow flower of purwosari pasuruan east java.  Seeing cases that often occur in the world of education makes researchers want to know the forms and factors of bullying in Mts. Darut Taqwa 02 Purwosari Pasuruan and the implementasies of moral akidah teachers in overcoming them. The purpose of this study was to introduce the strategy of moral teachers in overcoming bullying  cases in Mts. Darut Taqwa 02 Purwosari Pasuruan.  The implementasies used include: exemplary, educational learning and cooperation with all teachers, staff and students themselves. The approach used by researchers in this study is a qualitative approach, while the research instruments used for data mining are observation, documentation, and interviews. The respondents in this interview were: Head of Mts. Darut Taqwa 02 purwosari pasuruan, Student Affairs, BP Teacher, Akidah Akhlak Teacher, Student mts. Darut Taqwa 02. From the results of the study, it was found that basically the forms of bullying that occurred in Mts. Darut Taqwa 02 Purwosari Pasuruan were divided into two forms. First, verbal bullying Second, bullying physically.  The factors that cause bullying in Mts. Darut Taqwa 02 Purwosari Pasuruan such as, new students, students who do not get along, students who have physical deficiencies and students who do not have a certain group or groups.  The strategy used by the moral teacher is quite helpful in overcoming bullying cases.  Of course, by placing implementasies in the right class, so that students can understand and can create a calm and peaceful educational environment.